Woman singing with a band - Unknown:::Creator::::::::::::
Photograph shows what appears to be an African American woman singing with what a appears to be primarily a brass band in an outdoor setting. The director is directing the band behind and to the left of the singer. There are balloons in the foreground and one of them is a y-Walk balloon.